Canada ebook - Ford, Richard (2012)
The only writer ever to win both the Pulitzer Prize and Pen/Faulkner Award for a single novel (Independence Day) Richard Ford follows the completion of his acclaimed Bascombe trilogy with Canada. After a five-year hiatus, an undisputed American master delivers a haunting and elemental novel about the cataclysm that undoes one teenage boy's family, and the stark and unforgiving landscape in which he attempts to find grace. A powerful and unforgettable tale of the violence lurking at the heart of the world, Richard Ford's Canada will resonate long and loud for readers of stark and sweeping novels of American life, from the novels of Cheever and Carver to the works of Philip Roth, Charles Frazier, Richard Russo, and Jonathan Franzen.